Social Work and policy practice: group reflection and policy inquiry - Tony Evans (Social Work & Society, 2022)
Social policy in social work can be taught as rules articulated in documents.  But the policy work in professional practice is more complex - it involves not only knowing what policy says but also how it works and how to make it work. Social work tends to be located within street-level organisations where policy and its implementation are iterative and interlinked. It's a context where policy is found not only in documents but also in the level of finance, organisational structures, and the deployment of human resources. Policy is a site for critical practice - but contemporary approaches to critical reflection give insufficient attention to this.  Drawing on Dewey's ideas of democratic education and reflection as a group inquiry, I outline a structured pedagogic approach to group policy reflection that foregrounds this policy practice and offers a critical approach that supports analysis and action. Policy reflection enables group participants to: describe policy situations and dissect key policy messages; analyse policy messages, in the light of the demands of professional practice; and finally, work out how to respond, and how to act in line with critical professional commitments.